Answer:
see explanation
Step-by-step explanation:
(a)
Given
2k - 6k² + 4k³ ← factor out 2k from each term
= 2k(1 - 3k + 2k²)
To factor the quadratic
Consider the factors of the product of the constant term ( 1) and the coefficient of the k² term (+ 2) which sum to give the coefficient of the k- term (- 3)
The factors are - 1 and - 2
Use these factors to split the k- term
1 - k - 2k + 2k² ( factor the first/second and third/fourth terms )
1(1 - k) - 2k(1 - k) ← factor out (1 - k) from each term
= (1 - k)(1 - 2k)
1 - 3k + 2k² = (1 - k)(1 - 2k) and
2k - 6k² + 4k³ = 2k(1 - k)(1 - 2k)
(b)
Given
2ax - 4ay + 3bx - 6by ( factor the first/second and third/fourth terms )
= 2a(x - 2y) + 3b(x - 2y) ← factor out (x - 2y) from each term
= (x - 2y)(2a + 3b)
Answer:
112 calories per cup
Step-by-step explanation:
Let x = unit rate for calories per cup,
Then (3/4)*x = 84
and x = 84*(4/3) = 112 calories per cup
Answer:
12x+24
Step-by-step explanation:
by multiplying the number 6 into the term inside of the bracket gives 12x + 24
Answer:
5.333...
Step-by-step explanation:
You devide 8 by 15 and get the decimal form of this fraction.
It is 5.3 repeating
Answer:
86°
Step-by-step explanation:
180° is the sum of all angles in a triangle
The two angles given are 68° and 26°
The equation is : 180° - 68° - 26° = x°
180° - 68° - 26° = 86°
x° = 86°
If my answer is incorrect, pls correct me!
If you like my answer and explanation, mark me as brainliest!
-Chetan K